The Influence of the Mastery of Function Words on Students’ Reading Ability - Irmawati, Monica Ratna; Farida, Alief Noor (Universitas Negeri Semarang, 2020)
This study is an ex-post facto research which aims to find out the influence of the mastery of function words on reading ability of the seventh grade students of secondary school and to find out how the reading ability between students with adequate function words’ mastery and students with inadequate function words’ mastery is. The samples used in this research were two groups of students who have adequate and inadequate function words’ mastery. Each group consists of 30 students that is chosen by using stratified random sampling. In analysing the data, researcher used Independent Sample t-Test. The result shows that the mastery of function words significantly influences students’ reading ability. It is found that there is significant difference of students’ reading ability between students with adequate mastery in function words with those having inadequate mastery in function words. It is found that students with adequate function words’ mastery have better and higher ability in reading than students having inadequate function words’ mastery.